Sub-THz Luneburg lens enabled wide-angle frequency-coded identification tag for passive indoor self-localization. Issue 1 (13th February 2023) - Kadera, Petr; Sánchez-Pastor, Jesús; Schmitt, Lisa; Schüßler, Martin; Jakoby, Rolf; Hoffmann, Martin; Jiménez-Sáez, Alejandro; Lacik, Jaroslav
Abstract: An earlier version of this paper was presented at the 2021 15th European Conference on Antennas and Propagation (EuCAP) and was published in its Proceedings. This paper describes a design, fabrication, and characterization of a planar frequency-coded retroreflector for indoor localization. The retroreflector is fabricated in high-resistive silicon and consists of a Luneburg lens antenna and a photonic crystal high- Q resonator reflective layer, providing ranging and identification within the same tag and bandwidth. The Luneburg lens antenna presents a measured gain of 21.63 dBi at a design frequency of 240 GHz. The frequency-coded retroreflector allows for ranging in a continuous 130 degree angular range in azimuthal plane, with a discrete but repeatable two-resonance identification over multiples of 15 degree. Its maximum measured radar cross-section is −23.48 dBsqm at a frequency of 240 GHz. The retroreflective tag set in ideal line-of-sight situation is compared to a non-line-of-sight arrangement showing the influence of a metallic rod as an obstacle on the overall tag detection parameters. Finally, the successful read-out of the retroreflective tag is discussed in unknown environments, where no a-priori information is available.